Tuhan dalam Genggaman: Transformasi Pengalaman Spiritual dan Praktis Keagamaan di Era Kecerdasan Buatan (AI) - Nanang Qosim; Abdul Hamid (CV Kalimasada Group, 2025)
This study investigates the impact of integrating Artificial Intelligence (AI) and religious chatbots on spiritual experiences and traditional religious power structures. The phenomenon of Spiritual Hyper-reality emerges alongside the digitalization of rituals, where the boundary between the sacred and digital simulation becomes blurred. Utilizing qualitative and phenomenological methods—specifically in-depth interviews analyzed via Moustakas or Colaizzi models—this research explores individual interactions with theological algorithms as sources for scriptural interpretation and daily worship guidance. The findings reveal four primary outcomes: First, a shift in religious authority from individuals (such as clerics) to Algorithmic Authority, which is perceived as more objective. Second, while virtual assistants can maintain emotional depth, they tend to diminish the sense of mystery in spiritual interactions. Third, automated prayer applications create a Functional Rituality, increasing the frequency of worship while reducing its perceived sanctity. Fourth, inherent data biases in AI may reduce theological diversity and exclude minority groups. In conclusion, while AI expands spiritual access, reliance on algorithms risks turning spirituality into an instant commodity. This research highlights the necessity of ethical audits for religious algorithms and enhanced digital literacy within faith communities to preserve the authenticity of spiritual experiences.